At war with king alcohol : debating drinking and masculinity in the Civil War - Bever, Megan L. (Megan Leigh), 1984- (Civil War America (Series), 2022)
Using an array of sources - temperance periodicals, soldiers' accounts, legislative proceedings, and military records - Megan Bever explores the relationship between war, the practical realities of drinking alcohol, and temperance sentiment within the United States.